2009
DOI: 10.1086/599364
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evidence for Serotype‐Independent Acquired Immunity to Pneumococcal Carriage

Abstract: Our findings are consistent with the hypothesis that serotype-independent protective immunity is stimulated in young children by previous pneumococcal carriage and reduces the rate of new colonization. This immunity has the potential to modulate the development of carriage, irrespective of the colonizing serotype, and to do so starting early in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Mice immunized with WT-BCG or rBCG Mix with or without a booster dose of rMix, rBCG 0148/rSP 0148, or rBCG 2108/rSP 2108 were challenged by intranasal inoculation with the virulent serotype 3 pneumococcal strain WU2 (32) while the mice were under anesthesia. Mice that received saline and Al(OH) 3 were used as a control. In this model, mice aspirate the inoculum into the lungs and develop illness by the third day after infection.…”
Section: Resultsmentioning
confidence: 99%
“…Mice immunized with WT-BCG or rBCG Mix with or without a booster dose of rMix, rBCG 0148/rSP 0148, or rBCG 2108/rSP 2108 were challenged by intranasal inoculation with the virulent serotype 3 pneumococcal strain WU2 (32) while the mice were under anesthesia. Mice that received saline and Al(OH) 3 were used as a control. In this model, mice aspirate the inoculum into the lungs and develop illness by the third day after infection.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have suggested that immunity to pneumococcal colonization and disease develops in a manner that is not specific for the pneumococcal capsular serotype (7,14). To assess whether different pneumococcal serotypes induce distinct T helper cytokine profiles in the same donor, we infected cocultures with strains belonging to four different pneumococcal serotypes (2, 4, 9V, and 14) and measured IFN-␥ and IL-17 levels in the supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally acquired immunity is multifactorial; nonspecific antipneumococcal immunity develops alongside serotype-specific immunity in children through mechanisms that have not been entirely elucidated (34). In young infants with immature anti-CPS responses, epidemiological studies have suggested that nonspecific immunity predominates (35), while serotype-specific immunity comes to the fore in older children (32). In adulthood, both epidemiologic and controlled human infection studies have suggested that serotype-specific immunity plays a major role (33,36).…”
Section: Pneumococcal Colonization and Naturally Acquired Antipneumocmentioning
confidence: 99%